Can market-based approaches to technology development and dissemination benefit women smallholder farmers? A qualitative assessment of gender dynamics in the ownership, purchase, and use of irrigation pumps in Kenya and Tanzania - Njuki, Jemimah; Waithanji, Elizabeth M.; Sakwa, Beatrice; Kariuki, Juliet B.; Mukewa, Elizabeth; Ngige, John (International Food Policy Research Institute, 2014)
This paper reports findings from a qualitative study undertaken in Tanzania and Kenya to examine women’s access to and ownership of KickStart pumps and the implications for their ability to make major decisions on crop choices and use of income from irrigated crops. Results from sales-monitoring data show that women purchase less than 10 percent of the pumps and men continue to make most of the major decisions on crop choices and income use. These findings vary by type of crop, with men making major decisions on high-income crops such as tomatoes and women having relatively more autonomy on crops such as leafy vegetables.